Evaluation of TIG dental welding applied to Ti-6Al-4V alloys with different diameters: Analysis by Ultimate Tensile Strength, Vickers Hardness, and Finite Element Method (Research, Society and Development, 2021)
There is limited information in literature regarding the accomplishment of Ti-6Al-4V TIG joints welded in prefabricated bars applied to dentistry. Evaluate the ultimate tensile strength and Vickers hardness of Ti-6Al-4V alloy subjected to TIG (Tungsten Inert Gas) welding technique in different diameters. Material and methods: Forty-five specimens were prepared and divided into 5 groups: control group (CG) (n=5), with intact bars in a diameter of 3.0mm, and groups TIG2.5, TIG3, TIG4, TIG5 (n=10) with diameters of 2.5, 3, 4 and 5 mm respectively, welded with TIG in a pulse of 10(ms) and in a depth of 3(A). The specimens were tested by both radiographic inspection and penetrating liquids. After that, they were tested by ultimate tensile strength (UTS) and the elongation percentage (EP) was obtained. Images from fractured samples were taken and the welded areas percentage (WAP) was calculated. Random images were also taken by scanning electron microscope (SEM). Vickers hardness was obtained for base metal (BM), Heat affected zone (HAZ) and Welded zone (WZ). Finite element models were constructed. One-way Anova, Dunnet and Tukey tests (α=.05) were used for statistical analysis of UTS, WAP and EP for different groups and for differences in regions (BM, HAZ and WZ). Finite element models were developed in a workbench environment with boundary conditions simulating a tensile test. The majority of the specimens showed internal voids on radiographic inspection, but porosities or groves were not observed on their surface on penetrant liquid test. Most of the samples fractured in the welded area. The 1-way ANOVA showed significant differences among the groups for UTS, WAP and EP values (P